2016
DOI: 10.1128/aac.03042-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility to Ceftazidime-Avibactam of Carbapenem-Nonsusceptible Enterobacteriaceae Isolates Collected during the INFORM Global Surveillance Study (2012 to 2014)

Abstract: bThe activity of ceftazidime-avibactam was assessed against 961 isolates of meropenem-nonsusceptible Enterobacteriaceae. Most meropenem-nonsusceptible metallo-␤-lactamase (MBL)-negative isolates (97.7%) were susceptible to ceftazidime-avibactam. Isolates that carried KPC or OXA-48-like ␤-lactamases, both alone and in combination with extended-spectrum ␤-lactamases (ESBLs) and/or AmpC ␤-lactamases, were 98.7% and 98.5% susceptible to ceftazidime-avibactam, respectively. Meropenem-nonsusceptible, carbapenemase-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 28 publications
11
96
1
6
Order By: Relevance
“…from 3.2% in 2005 to 13.1% in 2010 ( P <0.05) 8. More recently, in a 3-year global surveillance program of hospitalized patients from 2012 to 2014 (INFORM), 15.7% (754/34,062) of all Enterobacteriaceae isolates were molecularly confirmed as ESBL producing, with similar results from 2011 to 2013 in US hospitals alone (12.4% of all Enterobacteriaceae, 1,696/13,692) 911. When stratified by infection type, ESBL rates of 10.4% for E. coli and 16.3% for Klebsiella pneumoniae have been observed for cIAI, consistent with overall prevalence 12.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…from 3.2% in 2005 to 13.1% in 2010 ( P <0.05) 8. More recently, in a 3-year global surveillance program of hospitalized patients from 2012 to 2014 (INFORM), 15.7% (754/34,062) of all Enterobacteriaceae isolates were molecularly confirmed as ESBL producing, with similar results from 2011 to 2013 in US hospitals alone (12.4% of all Enterobacteriaceae, 1,696/13,692) 911. When stratified by infection type, ESBL rates of 10.4% for E. coli and 16.3% for Klebsiella pneumoniae have been observed for cIAI, consistent with overall prevalence 12.…”
Section: Introductionmentioning
confidence: 60%
“…While antibiotics within the carbapenem class have a broad spectrum of antimicrobial activity and have traditionally been considered the agents of first choice for confirmed or suspected infection with ESBL producers, reports of carbapenem nonsusceptibility have also been increasing, representing 2.8% (961/34,062) of all Enterobacteriaceae based on INFORM data 9,10. Treatment of P. aeruginosa is fraught with similar challenges, with 15.7% (310/1,971) of P. aeruginosa isolates collected 2011–2012 from 32 US medical centers characterized as MDR.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluating the activity of ceftazidime-avibactam against 961 CRE isolates demonstrated that >97% of isolates were susceptible to the agent; its activity was only compromised by NDM-producing isolates. 86 However, clinical trials that led to approval of this agent included very few CRE infections or transplant/hematologic oncology patients. Clinical data to assess the effectiveness of this new agent for CRE infections and its effectiveness in immunocompromised hosts are urgently needed.…”
Section: Cre In Patients With Hematologic Malignancies and Haematopoimentioning
confidence: 99%
“…[13][14][15] This paper reports the primary data from the international, randomised phase 3 REPROVE trial (NCT01808092) evaluating the efficacy and safety of ceftazidime-avibactam versus meropenem in the treatment of NP, including ventilator-associated pneumonia (VAP).…”
Section: Introductionmentioning
confidence: 99%